2017
DOI: 10.36076/ppj.2017.e314
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Local Brain Activity Beyond the Pain Matrix in Postherpetic Neuralgia Patients: A Resting-State Functional MRI Study

Abstract: Background: Postherpetic neuralgia (PHN) patients suffer debilitating chronic pain, hyperalgesia, and allodynia, as well as emotional disorders such as insomnia, anxiety, and depression. The brain structure and functional basis of PHN are still not fully understood. Objectives: To identify the changes of regional brain activity in resting-state PHN patients using regional homogeneity (ReHo) and fractional aptitude of low-frequency fluctuation (fALFF) methods. Correlations between spontaneous pain intensity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…In addition to the precuneus/PCC, decreased ALFF values were also detected in the right MTG of both patient groups. This finding was consistent with previous studies which reported functional impairment of the right MTG in patients with PHN and HZ (11,12,17). However, there was no significant difference in ALFF between HZ and PHN.…”
Section: Significant Decrease In Spontaneous Neuronal Activity In Patsupporting
confidence: 94%
See 3 more Smart Citations
“…In addition to the precuneus/PCC, decreased ALFF values were also detected in the right MTG of both patient groups. This finding was consistent with previous studies which reported functional impairment of the right MTG in patients with PHN and HZ (11,12,17). However, there was no significant difference in ALFF between HZ and PHN.…”
Section: Significant Decrease In Spontaneous Neuronal Activity In Patsupporting
confidence: 94%
“…In this study, a significant decrease of ALFF in the right MFG was found in patients with PHN, but not in patients with HZ. This result is consistent with previous studies that decreased ALFF value and cerebral blood flow in the MFG were detected in the patients with PHN (5,12). The patients with PHN also showed notably abnormal tissue microstructure in the MFG (9).…”
Section: Significant Decrease In Spontaneous Neuronal Activity In Patsupporting
confidence: 93%
See 2 more Smart Citations
“…Over the last decade, functional MRI (fMRI) has been increasingly applied in studying abnormal brain activity of HZ and PHN patients (Geha et al, 2007, 2008; Liu et al, 2013; Zhang et al, 2014; Jiang et al, 2016; Cao et al, 2017a, 2018; Yu and Yu, 2017; Hong et al, 2018). By contrast, few structural changes of these patients, which potentially underlie the functional abnormalities, have been explored.…”
Section: Introductionmentioning
confidence: 99%